Body Boundaries Education for the Prevention of Sexual Violence in Elementary School Children: Edukasi Body Boundaries untuk Pencegahan Kekerasan Seksual pada Anak Sekolah Dasar - Muhammad Salim Mangunsong; Lulus Rahayu; Rima Mas’ula; Agna Dewi; Brett Aaron Huggins (LP2M Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2026)
This community service activity aimed to enhance elementary school children's understanding of body boundaries as an effort to prevent sexual violence. This education was motivated by the persistently high number of child sexual abuse cases in Indonesia and the lack of children's knowledge about which body parts can and cannot be touched. The method used was service-learning with a participatory approach involving Community Service Program (KKN) students from UIN Syekh Wasil Kediri Kediri as facilitators. The activity was conducted at SDN 1 and SDN 2 Purwodadi Village, Purwoasri District, from July to August 2025. Participants were students in grades 1 to 6, ranging in age from 7 to 12 years. The material was delivered through interactive lectures, visual media (illustrated PowerPoint presentations, animated videos), educational songs, quiz games, and role-playing simulations to train children to refuse inappropriate touch. Evaluation was carried out through pre-tests, post-tests, and observation of active participation. The results showed a significant improvement in participants' understanding, where students who initially had low knowledge about body boundaries became more aware of private body parts, could distinguish between good and bad touch, and had the courage to say